Oxidation kinetics of copper leadframes - Nirmal Kaur Waalib-Singh. (2011)
Copper-base alloys are of interest for high strength and high electrical and high thermal conductivity applications. However, their usage is usually limited by severe oxidation attack. The objective of the present study was to advance the fundamental understanding of the correlation between oxidation kinetics, oxide composition and surface morphology through theoretical considerations by the experimental investigation of a common industrial copper-alloy leadframe, the KLF125. The KLF 125 was oxidised in a thermogravimetric analyser, in the temperature range of 200 - 700 °C and oxygen flowrate of 15 - 55 psi. The effect of temperature on the scale morphology was observed via scanning electron microscopy and structural information obtained by X-ray diffraction.